Problems of national character in culture and literature of Kazakhstan and India - Shoinzhanova, M.T.; A.Ualtaeva, A.Derbisali, S.Kalkabaeva,; Belgozha, E. (Opción, 1970)
The article is devoted to scientific research and analysis of national characteristics and features of Kazakh-Indian literature based on the content and conceptual understanding of the works of world-famous thinkers. The work of writers and poets of the two countries is generalized, in which the main idea is the assertion that the national features of the mentality are formed depending on the environment, the geographical place of birth of the characters in their works. In particular, traditions and customs about the genesis and development of the status of heroes in the Kazakh-Indian society were analyzed.